Seni dalam Ruang Imaji : Mediasi Digital dan Perubahan Format Pertunjukan pada Taman Budaya Aceh Selama Pandemi - Afifuddin Afifuddin; Rasyidin Rasyidin; Aris Munandar (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The COVID-19 pandemic triggered a significant transformation of performing arts in Aceh, particularly through Taman Budaya Aceh, which shifted its stage activities into digital formats. This study aims to describe the processes of digital mediation, changes in production formats, audience engagement patterns, and the archival function of cultural performances through Taman Budaya Aceh’s official YouTube channel. Using a qualitative descriptive case study design, the research analyzed 12 performance videos produced and uploaded between 2020–2022 through visual and narrative analysis. The findings reveal three key aspects: first, the shift from offline to online production created a new aesthetic based on camera work and editing; second, audiences transformed into mediatized participants through comments, likes, and replays; third, digital platforms functioned as cultural repositories, expanding access and strengthening the preservation of performances. These findings highlight that digitalization of performing arts is not merely an emergency response, but an integral part of constructing a sustainable arts ecosystem in the digital disruption era.